Neuropsychiatric Involvement in Juvenile-Onset Systemic Lupus Erythematosus - Mohammad-Amin Khajezadeh; Gholamreza Zamani; Bobak Moazzami; Zahra Nagahi; Mahdie Mousavi-Torshizi; Vahid Ziaee (Neurology Research International)
Objective. Systemic lupus erythematosus (SLE) is a complex autoimmune disorder characterized by multisystem involvement, including the nervous system. In the present study, we aimed to assess neuropsychiatric manifestations in juvenile-onset systemic lupus erythematosus (JSLE) in Iran. Methods. One hundred and forty-six pediatric onset patients with SLE who had registered in our pediatric rheumatology database were evaluated prospectively and cross sectionally within 2013-2015. Data including sex, age, age at the time of diagnosis, age at the time of study, physical examination, laboratory review, and neuropsychiatric inventory were extracted from this database. Classification of neuropsychiatric JSLE was according to the 1999 American College of Rheumatology (ACR) neuropsychiatric manifestations of SLE case definitions. Result. A total number of 41 patients with neuropsychiatric symptoms were selected. The patients’ average age was 12.2 years. The most common neuropsychiatric symptoms were seizures, migraine, and depression. The mean age at the onset of symptoms was 10.2 ± 3 years. Mean follow-up period was 57±34 (range: 12-120) months. From 41 SLE patients, 18 (43.9) presented symptoms at the time of diagnosis. In thirteen (31.7%) patients, neurological symptoms were developed more than 1 year after SLE diagnosis. Headache was the most common feature (13%), followed by seizure (9.5%) and chorea (3.4%). Other neurological manifestations included cranial nerve involvement (0.7%), loss of consciousness (2.7%), and impaired deep tendon reflex neuropathy (2.5%). The least common neuropsychiatric JSLE manifestation was aseptic meningitis seen in only one patient (0.7%). Conclusion. The presence of headache, mood disorders, psychosis, depression, and other neuropsychological manifestations in a patient with JSLE should prompt investigations into diagnosis of the primary nervous system involvement in order to reduce mortality and morbidity.